An Interview with Sarojini Sahoo - Dr Shivani Vashist (International Journal of Advanced Science and Technology, 2020)
The interview of Sarojini Sahoo was taken as a part of doctoral research work which was undertaken under my supervision. The intention of taking the interview was to know Sarojini Sahoo’s views on Feminism as the research work was focused on short stories written by her from a feminist perspective. Though it was difficult meeting her physically, the interview was taken through electronic media. Her frank and direct answers throw light on her views and her approach towards her characters.